2019
DOI: 10.1111/btp.12661
|View full text |Cite
|
Sign up to set email alerts
|

The influence of historical dispersal on the phylogenetic structure of tree communities in the tropical Andes

Abstract: We test for evidence of the Tropical Niche Conservatism or the Out of The Tropics hypotheses in structuring patterns of tree community composition along a 2000 + meter elevational gradient in the northern tropical Andes. By collecting and integrating data on the presence–absence of tree species within plots with phylogenetic information, we analyzed the following: (a) patterns of phylogenetic dispersion and species diversity along the elevational gradient based on indexes of net relatedness, nearest taxon rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
(65 reference statements)
5
21
0
Order By: Relevance
“…We found a humped‐shaped relationship between the phylogenetic diversity (PDz) of forests and elevation. This pattern is consistent with the phylogenetic diversity vs. elevation relationships observed in other Neotropical mountain ecosystems (Gonzalez‐Caro et al 2014, Qian 2014, Qian and Ricklefs 2016, Ramirez et al 2019) and lends support for the hypothesis that tropical highlands of communities contain species of mixed biogeographic affinities (i.e., tropical and temperate). Overall, we observed a strong influence from both Godwanian and Laurasian biogeographic clades on the structure of the Neotropical highland tree communities (Gentry 1982, van der Hammen and Cleef 1983).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found a humped‐shaped relationship between the phylogenetic diversity (PDz) of forests and elevation. This pattern is consistent with the phylogenetic diversity vs. elevation relationships observed in other Neotropical mountain ecosystems (Gonzalez‐Caro et al 2014, Qian 2014, Qian and Ricklefs 2016, Ramirez et al 2019) and lends support for the hypothesis that tropical highlands of communities contain species of mixed biogeographic affinities (i.e., tropical and temperate). Overall, we observed a strong influence from both Godwanian and Laurasian biogeographic clades on the structure of the Neotropical highland tree communities (Gentry 1982, van der Hammen and Cleef 1983).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we expect the contribution from temperate immigrant clades to the total AGB of forests to be greater in the highlands than in the lowlands because of the greater climatic similarity between high‐latitude and tropical high‐elevation systems (Körner 2007, Feeley and Stroud 2018). Likewise, the mixing of clades from the tropical lowlands with temperate immigrants should produce more phylogenetic diversity in the highlands than in the lowlands (Ramirez et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, our study is the first effort to explicitly test the role that diversification before and after the origin of the environmental gradient (i.e., the uplift of the Central Andes) had on community structure across elevations. While previous studies have not tested the role of mountain uplift directly, our results are supported by previous research of Andean communities, which have suggested an important role for niche conservatism in community assembly across elevations (Graham et al, 2009;Hardy et al, 2012;Jin et al, 2015;Ramírez et al, 2019;Worthy et al, 2019;Bañares-de-Dios et al, 2020). A recent important study in this respect is that by Segovia et al (2020), who demonstrated a clear link in the phylogenetic composition of Andean tree communities to temperate regions of North and South America.…”
Section: Community Assembly Across Contrasting Elevations Is Dominatesupporting
confidence: 88%
“…Such studies demonstrate that both processes have occurred, but provide limited insights into how evolutionary history of individual clades contribute to the assembly of entire ecological communities and regional biotas. Second, studies that focus on the phylogenetic structure of Andean communities are relatively few and often fail to differentiate the effects of diversification before and after the emergence of the gradient (Graham et al, 2009;Parra et al, 2011;Bacon et al, 2018;Montaño-Centellas et al, 2019;Ramírez et al, 2019). To date, no study has sought to disentangle the relative importance of immigration and sorting of pre-adapted clades versus post-Andean uplift adaptive radiation in shaping the enormous variation in plant community composition across elevational gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Within montane landscapes, particularly at high elevations, evolutionary trends in distribution patterns are evident across a diversity of groups including microbes (Nottingham et al., 2018; Wang, Soininen, He, & Shen, 2012), ants (Machac, Janda, Dunn, & Sanders, 2011), ferns (Kluge & Kessler, 2011), and alpine plants (Li, Zhu, Niu, & Sun, 2014). TMFs show significant dissimilarity in evolutionary composition of tree communities across different elevations (Ramírez et al., 2019). In the tropical Andes, distribution limits are manifest within certain tree genera.…”
Section: Introductionmentioning
confidence: 99%